Etude De La Pertinence Des IG Comme Outil De Différenciation Des Produits De Terroir: CAS DE l’IGP Argane Dans La Ville d’Agadir Et Regions - El Bakkouri Bouchra; Souaf Malika; Elwazani Youssef (European Scientific Journal, ESJ, 2016)
The differentiation of local products is considered as a necessity nowadays given the standardization flows are increasing. This differentiation can be established especially through the Distinctive Signs of Origin and Quality (DSOQ). Our work has shown through the example of the PGI (Protected Geographical Indication) Argane, that GIs are a relevant tool for the differentiation of local products if they (GIs) are placed in a favorable context to their application. Our paper answers the following question: "To what extent geographical indications are meant as an effective tool for differentiation of local products: case of the PGI Argane in the city of Agadir and regions? To do so, we used an exploratory qualitative study through semi-structured interviews with a sample of people representing different stakeholders of Agadir and its regions, preceded of course by a literature review on the different key concepts.